2021
DOI: 10.1111/jfpe.13714
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on drying kinetics of ivy gourd using solar dryer

Abstract: Vegetable preservation through drying technology is an effective method to minimize wastage while satisfying the essential nutrition requirements. It is necessary to expand the existing technologies to preserve seasonal and regional specific vegetables. The present study is intended to find suitable conditions to increase preservation capacity through solar drying. A single slope solar dryer (SSSD) is designed, fabricated and ivy gourd is taken as a vegetable sample. Experiments are carried out in the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Furthermore, in open drying, the lack of an enclosed chamber reduces the ability to trap and channel heat for drying. 28 Also, the decreasing trend of moisture content with time was observed by Singh et al…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, in open drying, the lack of an enclosed chamber reduces the ability to trap and channel heat for drying. 28 Also, the decreasing trend of moisture content with time was observed by Singh et al…”
Section: Discussionmentioning
confidence: 77%
“…Dried samples increase the self-life, easy to storage and transport facilities, and this will decrease the cost and waste of the samples. [40][41][42][43] From, Figure 3 44 Elavarasan et al, 45,46 Elavarasan and sendhil. 47 From Table 2, it is observed that the Ash content is highest for forced convection drying (6.21 g/100 gm), followed by natural con-…”
Section: Resultsmentioning
confidence: 97%
“…The short drying period was achieved using high temperature retains inside the dryer reported by References[37–39]. Dried samples increase the self‐life, easy to storage and transport facilities, and this will decrease the cost and waste of the samples 40–43 …”
Section: Resultsmentioning
confidence: 99%
“…Advances in Materials Science and Engineering (2) Te amount of water content (W) removed [21][22][23][24] (3) Instantaneous moisture content Mt is calculated for time 't'…”
Section: Energy and Exergy Analysismentioning
confidence: 99%
“…[ [21][22][23][24] (5) Since equilibrium moisture (Me) is very less compared to initial moisture MR � (M t /M i ) [25] (6) Drying system efciency is a measure of a drying system's overall efcacy, indicating how well the input energy is used to dry the product; the energy usage for the blower can be used to calculate the forced convection dryer efciency…”
Section: Energy and Exergy Analysismentioning
confidence: 99%